Around The Arctic Circle
One in a series of boy's adventure stories centred round Frank Reade Jr., a young inventor-genius who created a robot, "Steam Man" and a succession of creatures including "Steam Horse", "Electric Dolphin" and innumerable flying and swimming wonders, including an electric airship, the "Eclipse". Aldine Romance of Invention, Travel, and Adventure Library, no. 108